Extrinsic vs. Intrinsic Regimes Shifts in Shallow Lakes: Long-Term Response of Cyanobacterial Blooms to Historical Catchment Phosphorus Loading and Climate Warming - Vermaire, Jesse C.; Taranu, Zofia E.; MacDonald, Graham K.; Velghe, Katherine; Bennett, Elena M.; Gregory-Eaves, Irene (Frontiers in Ecology and Evolution, 2017)
To evaluate the relative influence of intrinsic and extrinsic factors on ecosystem dynamics and regime shifts, we examined the algal response to historical catchment phosphorus loading from two shallow lakes located in Quebec, Canada. Roxton Pond is a eutrophic shallow lake with submerged macrophytes, and Lake Petit Saint-François (PSF) is a hypereutrophic shallow lake with no submerged macrophytes. Specifically, we inferred past cyanobacteria dynamics using pigment analyses, and tested whether the most parsimonious response model for cyanobacteria dynamics was congruent with the response model for phosphorus loading to the catchment. For both lakes, we found that an abrupt increase in cyanobacteria concentration lagged behind the initial increases in agricultural phosphorus use in the catchment as well as climate warming by over a decade. The delayed cyanobacterial response to these external drivers, observed in both lakes, suggests that intrinsic factors more than likely played important roles in ecosystem dynamics. These results show that cyanobacteria dominance in shallow lakes can be brought on by intrinsic responses to catchment phosphorus loading, climate warming, or both, but the timing depends on the antecedent conditions and the magnitude of the external forcing.